Modalities of Deployment of Telecommunications Infrastructure - Correa, Alexander (2017)
This study is aimed at investigating the firm’s decisions about the degree of quality improvements for advanced technology services when other approaches to infrastructure deployment, especially co-investment, act as alternative ways to launch new services. The model developed in this study considers the asymmetry of firms. This study shows that co-investment results in greater consumer welfare than fully distributed cost regulation, even though investment levels in quality improvements are lower. However, compared to individual investment, co-investment produces a deterioration in quality improvements when infrastructure sharing induces a considerable amount of incremental costs. The regulator should monitor co-investment agreements to avoid situations of tacit collusion especially when firms exhibit cost asymmetry in the deployment of advanced technology.